1999
DOI: 10.1111/j.1151-2916.1999.tb02238.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Content in ß‐Si3N4 Crystal Lattice

Abstract: and subsequent acid treatments that removed the secondary phases. The lattice oxygen contents of these crystals were determined by the hot-gas extraction method to be 0.258 ± 0.006 and 0.158 ± 0.003 wt% for the additive compositions of Y 2 O 3 :SiO 2 = 1:2 and 2:1, respectively. The oxygen dissolved in the ␤-Si 3 N 4 crystal lattice as much as in the ␣-Si 3 N 4 crystral lattice prepared by the chemical vapor deposition process and in the AlN crystal lattice that exhibited high thermal conductivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 13 publications
2
34
0
1
Order By: Relevance
“…SEM images of the composite material were obtained by background-scatter electron (BSE). The amount of oxygen impurities dissolved in the Si 3 N 4 particles, or lattice oxygen content, was determined by the method reported by Kitayama et al 18) using a hot-gas extraction analyzer (Model TC-436 and EF-400, LECO Co., USA). In this method, the sample was placed in a graphite crucible, followed by heating to 2500°C in 5 min in a flowing argon atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SEM images of the composite material were obtained by background-scatter electron (BSE). The amount of oxygen impurities dissolved in the Si 3 N 4 particles, or lattice oxygen content, was determined by the method reported by Kitayama et al 18) using a hot-gas extraction analyzer (Model TC-436 and EF-400, LECO Co., USA). In this method, the sample was placed in a graphite crucible, followed by heating to 2500°C in 5 min in a flowing argon atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…18) Kitayama et al reported a correlation between lattice oxygen content and thermal resistivity (the inverse of thermal conductivity) of crystalline ¢-Si 3 N 4 .…”
Section: Characteristics Of Compositesmentioning
confidence: 99%
“…Three measurements were performed for all samples and the average is used as the measured value. Amount of oxygen distributed in Si 3 N 4 lattice (lattice oxygen) was approximated by Gaussian peak separation of the evolution curve during heating after Kitayama et al 9 using the HF-treated powders (46% HF, 3 h at 333 K and 50% H 2 SO 4 , 6 h at 373 K).…”
Section: Methodsmentioning
confidence: 99%
“…It was found that grain growth of ␤-Si 3 N 4 shifts from interfacial-reaction- controlled to diffusion-controlled as the ionic radius of the rareearth element decreases, and later that the activation energy for the interfacial reaction linearly decreases with decreasing ionic radius. 24 This is the reason why the phase transformation rate of a sample sintered with La 2 O 3 , the largest among the rare-earth ions, is extremely slow, and why mean grain size (Ϸ mean grain width) increases with decreasing ionic radius of the rare-earth ions. The reason why the mean grain sizes of samples sintered with Yb 2 O 3 and Sc 2 O 3 are somewhat smaller than Y 2 O 3 , even though their grain growth is expected to be more diffusion-controlled, can be attributed to their higher viscosity of the liquid phase due to their higher cationic field strength.…”
Section: (1) Effect Of Microstructure On Thermal Conductivitymentioning
confidence: 99%